2018
DOI: 10.3390/s18092969
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Estimation of Rebar Diameter and Cover Thickness by a GPR-EMI Dual Sensor

Abstract: Precise characterization of reinforcing bars (rebars) in a concrete structure is of significant importance for construction quality control and post-disaster safety evaluation. This paper integrates ground-penetrating radar (GPR) and electromagnetic induction (EMI) methods for simultaneous estimation of rebar diameter and cover thickness. A prototype of GPR-EMI dual sensor is developed, and a calibration experiment is conducted to collect a standard EMI dataset corresponding to various rebar diameters and cove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(17 citation statements)
references
References 41 publications
0
15
0
2
Order By: Relevance
“…Those images can be obtained from a grid of B-scans obtained in profile lines separated by 10 cm [244]. Combining GPR with other techniques such as electromagnetic induction, it is possible to determine the position of the rebar, the cover thickness, and the rebar diameter [245]. The main limitation occurs in the case of a densely-meshed rebar, requiring antennas with narrower transmission energy cones.…”
Section: Rebar Detection and Corrosionmentioning
confidence: 99%
“…Those images can be obtained from a grid of B-scans obtained in profile lines separated by 10 cm [244]. Combining GPR with other techniques such as electromagnetic induction, it is possible to determine the position of the rebar, the cover thickness, and the rebar diameter [245]. The main limitation occurs in the case of a densely-meshed rebar, requiring antennas with narrower transmission energy cones.…”
Section: Rebar Detection and Corrosionmentioning
confidence: 99%
“…Due to that, additional NDT methods (e.g. eddy current [11], electromagnetic induction [14], [15]) need to be applied in the field to complement GPR, raising the overall computational and operational costs, and adding complexity to the acquisition.…”
Section: Introductionmentioning
confidence: 99%
“…Zhou et al [16] used GPR in combination with the electromagnetic induction (EMI) method to accurately locate reinforcing bars. Chang et al [17] reported a physical model based on the use of digital image GPR for measuring the radius of reinforcing steel bars in concrete.…”
Section: Introductionmentioning
confidence: 99%
“…For detection and localization of reinforced bars, Remote Sens. 2021, 13, 2020 2 of 16 Liu et al [21] and Giannakis et al [22] utilized machine-learning methods to estimate the diameter of reinforcements. Moreover, the evaluation of concrete parameters is an essential research subject.…”
Section: Introductionmentioning
confidence: 99%